2016
DOI: 10.1371/journal.pntd.0005188
|View full text |Cite|
|
Sign up to set email alerts
|

Synchrony of Dengue Incidence in Ho Chi Minh City and Bangkok

Abstract: BackgroundHo Chi Minh City and Bangkok are highly dengue endemic. The extent to which disease patterns are attributable to local versus regional dynamics remains unclear. To address this gap we compared key transmission parameters across the locations.Methods and Principal FindingsWe used 2003–2009 age-stratified case data to inform catalytic transmission models. Further, we compared the spatial clustering of serotypes within each city. We found that annual case numbers were highly consistent across the two ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
(47 reference statements)
2
13
0
Order By: Relevance
“…The median age of notified dengue cases in Nha Trang was 11–20 years over the study period, which is younger than previously reported in northern Vietnam 7 and similar to estimates from hospitalized cases in southern Vietnam. 10 , 33 Together, these data are consistent with an overall increase in intensity of DENV transmission from the north of the country to the south.…”
Section: Discussionsupporting
confidence: 71%
“…The median age of notified dengue cases in Nha Trang was 11–20 years over the study period, which is younger than previously reported in northern Vietnam 7 and similar to estimates from hospitalized cases in southern Vietnam. 10 , 33 Together, these data are consistent with an overall increase in intensity of DENV transmission from the north of the country to the south.…”
Section: Discussionsupporting
confidence: 71%
“…As dengue outbreaks within a region can be synchronous, driven in part by large climatic shifts (e.g. El Niño) [33][34][35][36] , we sought to determine if recent ecological changes could have altered virus transmission potential by Ae. aegypti mosquitoes.…”
Section: Mosquito-borne Virus Surveillance and Transmission Potentialmentioning
confidence: 99%
“…Modeling work by Lourenco and Recker has recapitulated this concept, with evidence that the population dengue prevalence and stochastic events play strong roles in shaping DENV epidemics and that DENV epidemics could not be simplistically explained by DENV strain fitness alone [109,140]. Another study also found that many of the dynamics of DENV epidemics in a single dengue season in Ho Chi Minh City and Bangkok were synchronous, despite there being a distinctly different admixture of DENV serotypes in each city [141]. In sum, it is important to consider how a potential interaction between ecology, virology and population level immunity may shape certain DENV epidemics.…”
Section: What Are the Drivers Of Denv Evolution And Diversity?mentioning
confidence: 99%